MAPPING AND ANALYSIS OF SCIENTIFIC PRODUCTION ON ROAD SAFETY: MAPPING AND ANALYSIS OF SCIENTIFIC PRODUCTION ON ROAD SAFETY - Santos, Diego Vieira dos; Gonçalves, Wellington; Freitas, Rodrigo Randow de (Brazilian Journal of Production Engineering, 2020)
Bibliometric analysis is an important tool for visualizing knowledge on topics of interest relevant to society. In this article, we use this resource with the main objective of mapping and analyzing the knowledge produced on a topic of global relevance: traffic safety. In this sense, we conducted a search for articles published on the topic in the Scopus database, starting in 2011, considering the “Decade of Action for Traffic Safety 2011-2020”. 7,956 articles written in English were retrieved, from which the main countries, authors, sources, institutions and areas that addressed the topic of road safety were presented. Then, according to refining criteria, 26 articles were selected for the content analysis stage. This step was aided by the VOSviewer Software that contributed to the visualization of elements that were discussed. The results showed a preponderance of studies on human behavior in traffic, mainly violations due to excessive speed and alcohol consumption by drivers, in addition to the concern with pedestrian safety. There was a tendency towards a systemic approach to traffic safety, in order to consider multiple factors involved in this context, and not only the human factor. Therefore, the traditional 3E’s strategy of traffic safety has been expanded, with the inclusion of other E’s, in order to enable the formulation of more effective strategies and appropriate to the experienced scenario.